Cholera toxin B induces interleukin-1β production from resident peritoneal macrophages through the pyrin inflammasome as well as the NLRP3 inflammasome. (25th January 2019) - Orimo, Takashi; Sasaki, Izumi; Hemmi, Hiroaki; Ozasa, Toshiya; Fukuda-Ohta, Yuri; Ohta, Tomokazu; Morinaka, Mio; Kitauchi, Mariko; Yamaguchi, Takako; Sato, Yayoi; Tanaka, Takashi; Hoshino, Katsuaki; et al.
Abstract: Cholera toxin B (CTB) is a subunit of cholera toxin, a bacterial enterotoxin secreted by Vibrio cholerae and also functions as an immune adjuvant. However, it remains unclear how CTB activates immune cells. We here evaluated whether or how CTB induces production of a pro-inflammatory cytokine, interleukin-1β (IL-1β). CTB induced IL-1β production not only from bone marrow-derived macrophages (BMMs) but also from resident peritoneal macrophages in synergy with O111:B4-derived lipopolysaccharide (LPS O111:B4) that can bind to CTB. Meanwhile, when prestimulated with O55:B5-derived LPS (LPS O55:B5) that fails to bind to CTB, resident peritoneal macrophages, but not BMMs, produced IL-1β in response to CTB. The CTB-induced IL-1β production in synergy with LPS in both peritoneal macrophages and BMMs was dependent on ganglioside GM1, which is required for internalization of CTB. Notably, not only the NLRP3 inflammasome but also the pyrin inflammasome were involved in CTB-induced IL-1β production from resident peritoneal macrophages, while only the NLRP3 inflammasome was involved in that from BMMs. In response to CTB, a Rho family small GTPase, RhoA, which activates pyrin inflammasome upon various kinds of biochemical modification, increased its phosphorylation at serine-188 in a GM1-dependent manner. This phosphorylation as well as CTB-induced IL-1β productions were dependent on protein kinase A (PKA), indicating critical involvement of PKA-dependent RhoA phosphorylation in CTB-induced IL-1β production. Taken together, these results suggest that CTB, incorporated through GM1, can activate resident peritoneal macrophages to produce IL-1β in synergy with LPS through novel mechanisms in which pyrin as well as NLRP3 inflammasomes are involved. Abstract : CTB activates peritoneal macrophages via a novel inflammasome pathway